Challenges of transsphenoidal pituitary surgery in severe brachycephalic dogs - Van Stee, Lucinda L.; Van Rijn, Sarah J.; Galac, Sara; Meij, Björn P. (Frontiers in Veterinary Science, 2023)
Introduction Transsphenoidal hypophysectomy is the standard surgical technique for the excision of pituitary neoplasms. Anatomy may be more obscured in brachycephalic skull types due to the crowding of soft tissue and osseous structures. We describe the unique challenges to approach the sphenoid bone and localize the correct burr hole site in severe brachycephalic dogs. Materials and methods A single institution retrospective case series of brachycephalic dogs with pituitary-dependent hypercortisolism (PDH). Preoperative computed tomography enabled 3D-, and cross-sectional reconstruction to plan and dry-practice the position of the ideal burr hole in relation to the sella turcica, pterygoid hamular processes, and hard palate. Rostral burring of the caudal hard palate obscuring the direct sphenoid approach necessitated adaptations to the original transsphenoidal hypophysectomy procedure. Postoperative outcomes and complications with respect to those seen in mesocephalic dogs are described. Results Ten brachycephalic dogs including French Bulldogs (n = 9) and a single Dogue de Bordeaux were included. All dogs were diagnosed with PDH and had preoperative advanced imaging performed on the skull. All but one dog had an enlarged pituitary gland, with a median pituitary/brain value of 0.5 (range 0.21–0.9). A total of 11 transsphenoidal hypophysectomy procedures were performed in these 10 dogs. Rostral extension of the soft palate incision into the hard palate was performed to access the burr hole site on the sphenoid bone. Major complications included aspiration pneumonia (n = 1), severe gastroesophageal reflux (n = 1), and central nervous signs (=1). All dogs survived until discharge, with a median time to follow-up of 618 days (range 79–1,669 days). Seven dogs experienced long-term remission of PDH. Conclusion Brachycephalic dogs undergoing transsphenoid al hypophysectomy benefit from meticulous presurgical planning and extension of the approach into the caudal hard palate. Advanced surgical skills can render a good outcome in a technically challenging environment.